Determination of Trace Element Concentrations in Blood Samples and Their Correlation to Breast Cancer - Topdagi, Omer; Toker, Ozan; Bakirdere, Sezgin; Oz, Ersoy; Bursalioglu, Ertugrul Osman; Abuqbeitah, Mohammad; Demir, Mustafa; Icelli, Orhan (ATOMIC SPECTROSCOPY PRESS LTD, 2020)
The main purpose of this study was to investigate the possible differences in the concentrations of Al, Cu, Ca, Mg, Fe, Ni, and Pb in breast cancer patients and healthy control group. One blood sample each was collected from 40 adult female patients diagnosed with breast cancer and 40 healthy adult female individuals with no medical history of cancer. The concentrations of the elements Al, Cu, Fe, Ni, and Pb were determined by ICP-MS, while Ca and Mg were determined by ICP-OES. Statistical analysis was performed with the Kolmogorov-Smirnov normality test, the Mann-Whitney U test, and the Spearman's rank correlation test. It was observed that the concentrations of Cu and Mg in the breast cancer patients were significantly higher (p=0.000<0.05 and p=0.001<0.05, respectively) than for the healthy group, while the Al concentration was significantly lower (p=0.002<0.05) in the cancer patients. The Mg concentration in the control group and the patients was 33.60 +/- 4.51 and 38.10 +/- 9.69 mg/kg, respectively. The difference was statistically significant for Cu, Mg, and Al, whereas no difference was observed between the concentrations of Ca and Fe. Furthermore, a positive correlation was observed in breast cancer patients between the concentrations of (Al-Cu), (Al-Ca), (Fe-Mg), and (Cu-Ca).
Keywords: COPPER; SERUM; CALCIUM; IRON; ZINC; Spectroscopy